Grafiska dekaler : Utveckling av internationella brandskyddsdekaler för släcksystem i fordon - Kerttu, Greta (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
This report concerns a thesis of 15 credits for the Bachelor programme industrial design engineering, targeting product development, at Luleå University of Technology.The work was created in collaboration with the client Dafo Brand AB with the goal to create language independent safety labels for their fire supression system, something requested by their clients. Dafos labels has always been primarily text-based, but with exports around the world, both for them and their customers, the administration work would make it easier with less different language labels. The desire was to create uniform decals that are user-friendly, especially for the end user; the vehicle driver, whom need to understand the labels regardless of language.To create these stickers a design process have been used, where phases like pre-study, theory research, creative methods and concept development has been completed in order to develop the concept into a useful product. The phases has included, among other things, questionnaires, interviews, market research and creative methods to take out three concept which has then been examined in usability testing to see which conecpts were the best for the final conecpt.The result was a total of 12 labels with symbols for the fire supression system. The symbols are primarly selected on the basis of the market survey, international standards and the survey responses from the vehicle drivers. Denna rapport beskriver ett examensarbete på 15 högskolepoäng för högskoleingenjörsprogrammet teknisk design, inriktning produktutveckling, vid Luleå tekniska universitet.Arbetet skapades i samarbete med uppdragsgivaren Dafo Brand AB med målet att skapa språkoberoende säkerhetsdekaler för deras släcksystem, något som deras kunder efterfrågat på grund av administrationen med flera uppsättningar språkdekaler. Dafo har alltid haft främst textbaserade dekaler, men med exporter världen över, både för dem och deras kunder, skulle administrationsarbetet underlättas med färre artiklar. Önskemålen var att skapa ...